Systematic review of digital and non-digital non-pharmacological interventions that target quality of life and psychological outcomes in adults with systemic lupus erythematosus. (June 2021) - Chang, Angela; Winquist, Nathan W; Wescott, Annie B; Lattie, Emily G; Graham, Andrea K
Background: Patients with systemic lupus erythematous (SLE) experience psychological comorbidities and impaired quality of life (QOL). We conducted a systematic review to examine the efficacy of non-pharmacological interventions for improving psychological outcomes and/or QOL in patients with SLE. To expand on a previous systematic review in this area and enhance our understanding of efficacious interventions for this population, our search included quasi-experimental and experimental studies of interventions delivered or supported by remote methods (including digitally) or in person. Methods: A comprehensive literature search was conducted with a research librarian using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and was registered before data extraction on the international prospective register of systematic reviews PROSPERO Web site (CRD42020154962). The search included controlled-vocabulary and title/abstract terms related to non-pharmacological interventions for SLE published through October 2019 in MEDLINE (Ovid), Cochrane Library databases (Wiley), Embase (Elsevier), CINAHL (EBSCO), PsycINFO (EBSCO), Web of Science (Clarivate), ACM Digital (Association of Computer Machinery), and IEEE Xplore. Studies were synthesized using a systematic narrative synthesis framework. Risk of bias was assessed. Results: Twenty-three studies were included: 21 randomized controlled trials and two quasi-experimental studies. Non-pharmacological diet, physical activity, psychological, and course-based interventions improved QOL and psychological outcomes, and were delivered in traditional settings (e.g., hospital) or remotely. No studies assessing digital non-pharmacological interventions were identified in our search. Quality assessments showed serious risk of bias for the two quasi-experimental studies, and high risk of bias in a subset of experimental studies. Conclusions: Non-pharmacological interventions benefit patients with SLE. Future research should include more representative samples in rigorous evaluations and consider ways to incorporate digital technologies to increase accessibility.